Ethical considerations in utilizing eConsent in biomedical research - Catalán, Lucía; Pinilla, Nicole; Oliveira, Déborah (Revista Bioética, 2025)
Informed consent is crucial to uphold the autonomy of participants in healthcare research. Despite being widely used, electronic consent remains inadequately regulated in many countries, posing numerous ethical risks. This article aims to critically examine the ethical implications associated with using electronic consent and propose solutions to such issues. Ethical concerns include providing insufficient information for informed decision-making, limitations in assessing individual capacity to consent, communication barriers with participants, selection bias, difficulties in verifying participant identity, and breach of privacy and confidentiality. To address these concerns, a proactive approach must be adopted, anticipating and implementing measures to safeguard participant rights. Countries lacking specific regulations should prioritize the establishment of guidelines to ensure the ethical use of electronic consent in healthcare research.